Between cooperation and conflict: the national union of road transport workers in Lagos, Nigeria - Agbiboa, Daniel E. (Crime, law and social change, 2020)
Foregrounding urban public transport as a terrain of political action and meaning-making, this article explores the role and politics of the National Union of Road Transport Workers (NURTW) in Lagos, Nigeria’s commercial capital, located in the south-west of the country. Particular attention is paid to the ways in which political agency is being exercised at different levels (that is, both within the NURTW and towards workers and the state), the manner in which the union-state relationship is weaponized by both parties, and how the union is drawn into patronage networks that redistribute resources provided by the state. The analysis extends to the insecurities that road transport workers face on a daily basis in their struggle to navigate the extortionate power of the union-state alliance, and make ends meet.